Closet Ball Queen competition - Sahl, Ted (photographer):::Creator::::::::::::
Five female impersonators wearing evening gowns pose for a photograph during the "Closet Ball Queen" competition. Gerry Okeefe the winner of contest is flanked on both sides by the other four contestents. She is wearing a long white gown and lace robe.